Beneath the killing fields : exploring the subterranean landscapes of the western front - Leonard, Matthew (Pen & Sword Books, 2017)
Beneath the Killing Fields of the Western Front still lies a hidden landscape of industrialised conflict virtually untouched since 1918. This subterranean world is an ambiguous environment filled with material culture that that objectifies the scope and depth of human interaction with the diverse conflict landscapes of modern war. Covering the military reasoning for taking the war underground, as well as exploring the way that human beings interacted with these extraordinary alien environments, this book provides a more all-encompassing overview of the Western Front. The underground war was intrinsic to trench warfare and involved far more than simply trying to destroy the enemys trenches from below. It also served as a home to thousands of men, protecting them from the metallic landscapes of the surface. With the aid of cutting edge fieldwork conducted by the author in these subterranean locales, this book combines military history, archaeology and anthropology together with primary data and unique imagery of British, French, German and American underground defences in order to explore the realities of subterranean warfare on the Western Front, and the effects on the human body and mind that living and fighting underground inevitably entailed.